The prevalence of byssinosis among cotton workers in the north of Benin - HINSON, ANTOINE VICKKEY; SCHLÜNSSEN, VIVI; AGODOKPESSI, GILDAS; FAYOMI, EBOUM BENJAMIN (My University, 2014)
Background: Cotton is the main agricultural export product in Benin. Cotton dust is thus present in the air during the handling and processing of cotton. This dust contains a mixture of substances including ground up plant matter, fibres, bacteria, fungi, soil, pesticides, noncotton matter, and other contaminants. While cotton processing is decreasing in industrialized countries, it is increasing in developing countries. Cotton processing, particularly in the early processes of spinning, can cause byssinosis. Objective: To determine the respiratory effects of cotton dust exposure among cotton mill workers in Benin. Methods: In a cross-sectional study, 109 workers exposed to cotton dust and 107 unexposed workers were studied. The International Commission on Occupational Health (ICOH) questionnaire was used for data collection on respiratory symptoms. For each worker, crossshift pulmonary function was performed with a dry spirometer. Based on the severity of respiratory symptoms and spirometry byssinosis was defined and classified according to thecriteria of Schilling, et al. Results: The mean±SD age of the exposed and unexposed workers was 46.3±7.8 and 37.0±8.3 years, respectively (p<0.001). The mean FEV1 predicted value for the exposed and unexposed workers was 76.3% and 77.3%, respectively. The prevalence of grade 3 byssinosis was 21.1% (95% CI: 13.4–28.9) in exposed workers and 8.4% (95% CI: 3.1–13.7) in unexposed workers (p=0.006). On Mondays, the exposed workers had more respiratory symptoms than unexposed workers; for grade 3 byssinosis, the prevalence was 13.8% in exposed and 4.7% in unexposed workers (p=0.011). Conclusion: The prevalence of respiratory symptoms and byssinosis among cotton mill workers in Benin is high and needs prompt attention of health care workers and policymakers.
Keywords: Byssinosis; Cotton fiber; Respiratory function tests; Respiration disorders; Smoking; Occupational exposure; Benin